Can a Muslim Reject Evolution? A Theological Refutation of Common Ancestry - Nazir Ahmad Zargar (Penerbit Hellow Pustaka, 2025)
This paper critically examines Caner Taslaman’s argument that the Qur’ān is silent on Darwinian evolution and that Muslims can remain theologically neutral regarding human evolution. Taslaman contends that Ādam’s creation was a gradual process and that evolution does not conflict with Islamic teachings. In his chapter“Can a Muslim be an Evolutionist?” he claims that the creation of Ādam was ‘processive’, not instantaneous. The author further argues that Muslims should not have any reason to refute Darwinian evolution because the Qur’ān itself is silent about it. In contrast, this study argues that the concept of evolutionary common ancestry, especially human descent from animals, contradicts explicit Qur’ānic Āyāt, authentic Ḥadīth, and Ijmāʿ (unanimous scholarly consensus). Drawing upon classical and modern Qur’ānic Tafsīr, Ḥadīth interpretations, and scientific critiques of Darwinian gradualism, the paper affirms Ādam’s unique, instantaneous creation. It further highlights the theological and moral ramifications of rejecting this doctrine within Islam.